Studi Penerapan Aplikasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) - Suriani Suriani; Otniel Ketaren; Johansen Hutajulu (Journal of Telenursing (JOTING), 2023)
This study aims to determine the application of SIMRS in the Outpatient Polyclinic at the Cut Nyak Dhien Meulaboh Regional General Hospital (RSUD). The research method uses observation and in-depth interviews. The study results show that the benefits of SIMRS have been able to integrate data and be standardized according to the INa-CBgs coding. There still needs to be more staff managing SIMRS, it is necessary to improve facilities and infrastructure, especially a stable network, and the implementation of Monitoring and Evaluation is only carried out when there are complaints about the implementation of SIMRS. In conclusion, the performance of SIMRS in Cut Nyak Dhien Meulaboh Hospital has yet to be maximized. It is hoped that there will be a commitment to improving the Standard Operating Procedures regarding implementing SIMRS in Hospitals. Keywords: Application, SIMRS, Outpatient Poly